Lactobacillus johnsonii 6084 alleviated sepsis‐induced organ injury by modulating gut microbiota. Issue 11 (22nd July 2022) - Han, Shichao; Zheng, Haotian; Han, Fu; Zhang, Xiaowei; Zhang, Geng; Ma, Shuaijun; Liu, Kepu; Qin, Weijun; Wu, Gaofeng
Abstract: Sepsis is a public cause of death in intensive care unit patients. Probiotics were widely used to increase the survival rate of sepsis by a series of clinical research. The purpose of this research was to investigate the therapeutic effects of Lactobacillus johnsonii 6084 in septic mice. Sepsis mouse model was induced by LPS treatment. The influence of L. johnsonii 6084 on the protection of organ injury induced by sepsis was explored. Moreover, the composition of gut microbiota was studied to clarify the mechanism of L. johnsonii 6084 therapeutic effect on sepsis. L. johnsonii 6084 treatment could conspicuously decrease the mortality and organ injury of sepsis. The reduction of gut microbial diversity and richness in septic mice were moderated by the administration of 6084. The abundance of Bacteroidetes and Proteobacteria were change by LPS treatment while restored by L. johnsonii 6084. To conclude, probiotic 6084 may has optimistic result on reducing mortality of sepsis through rebalancing gut microbiota. Abstract : Probiotic Lactobacillus johnsonii 6084 has a positive effect on reducing mortality of sepsis through rebalancing gut microbiota.